PKA functions in metabolism and resistance to obesity: lessons from mouse and human studies. Issue 3 (September 2020) - London, Edra; Bloyd, Michelle; Stratakis, Constantine A
Abstract : Both direct and indirect evidence demonstrate a central role for the cAMP-dependent protein kinase (PKA) signaling pathway in the regulation of energy balance and metabolism across multiple systems. However, the ubiquitous pattern of PKA expression across cell types poses a challenge in pinpointing its tissue-specific regulatory functions and further characterizing its many downstream effects in certain organs or cells. Mouse models of PKA deficiency and over-expression and studies in living cells have helped clarify PKA function in adipose tissue (AT), liver, adrenal, pancreas, and specific brain nuclei, as they pertain to energy balance and metabolic dysregulation. Limited studies in humans suggest differential regulation of PKA in AT of obese compared to lean individuals and an overall dysregulation of PKA signaling in obesity. Despite its complexity, under normal physiologic conditions, the PKA system is tightly regulated by changes in cAMP concentrations upstream via adenylate cyclase and downstream by phosphodiesterase-mediated cAMP degradation to AMP and by changes in PKA holoenzyme stability. Adjustments in the PKA system appear to be important to the development and maintenance of the obese state and its associated metabolic perturbations. In this review we discuss the important role of PKA in obesity and its involvement in resistance to obesity, through studies in humans and in mouse models, with a focus on the regulation of PKA in energy expenditure, intake behavior, and lipid and glucose metabolism.